2021
DOI: 10.25299/sportarea.2021.vol6(2).6362
|View full text |Cite
|
Sign up to set email alerts
|

The fitness of middle age to the elderly based on body mass index and age in the new normal era

Abstract: Decrease in physical fitness occurs after the age of 30 years and factors that affect physical fitness include age, gender, BMI, waist circumference, hypertension, and diabetes mellitus. This study aims to determine the physical fitness of middle-aged to elderly people between 45-74 years based on BMI and age. This research is a descriptive study with quantitative methods. The sample of this research is men who are active in badminton activities in Rejang Lebong Regency, which are classified as middle age to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Physical fitness is an important indicator of a person's health status (Kapoor et al, 2022). Age is one of several elements that contribute to a person's declining level of physical fitness (Juliansyah et al, 2021), gender, body mass index (Ilsya et al, 2024) disease (Eichorn et al, 2018) and sleep quality (Lipert et al, 2021) as well as the environment and diet adopted. Several studies state that low physical fitness is the cause of the development of noncommunicable diseases (Lavie et al, 2019;Lee et al, 2012) such as cardiovascular disease, diabetes and so on and is at risk of causing death (Anderson & Durstine, 2019;Nieman & Sakaguchi, 2022).Because increasing fitness can provide beneficial effects for physical endurance, it is crucial to recognize the level of physical fitness and the suitable needs for students who are constantly engaged in demanding activities.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness is an important indicator of a person's health status (Kapoor et al, 2022). Age is one of several elements that contribute to a person's declining level of physical fitness (Juliansyah et al, 2021), gender, body mass index (Ilsya et al, 2024) disease (Eichorn et al, 2018) and sleep quality (Lipert et al, 2021) as well as the environment and diet adopted. Several studies state that low physical fitness is the cause of the development of noncommunicable diseases (Lavie et al, 2019;Lee et al, 2012) such as cardiovascular disease, diabetes and so on and is at risk of causing death (Anderson & Durstine, 2019;Nieman & Sakaguchi, 2022).Because increasing fitness can provide beneficial effects for physical endurance, it is crucial to recognize the level of physical fitness and the suitable needs for students who are constantly engaged in demanding activities.…”
Section: Introductionmentioning
confidence: 99%
“…Res. 2(1);59-71 (2023) hypertension, and diabetes mellitus, lead to decreased physical fitness (Juliansyah et al, 2021). Furthermore, there is a link between the body mass index (BMI) of senior people and their age, gender, and BMI-based measures of physical fitness (Oktriani et al, 2020), dietary intake and physical activity (Erliana & Hartoto, 2019;Hartanti & Mawarni, 2020), and sleep quality (Gunarsa & Wibowo, 2021), overweight (Galan-Lopez et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness is a key predictor of adolescents' current and future health status (Rubín, Suchomel, Cuberek, Dušková, & Tláskalová, 2017). Age, gender, BMI, waist circumference, hypertension, and diabetes mellitus are all variables that contribute to a decline in physical fitness (Juliansyah, Sugiyanto, & Hita, 2021). Several studies have found that a lack of physical fitness is a factor in the development of noncommunicable illnesses (Lavie, Ozemek, Carbone, Katzmarzyk, & Blair, 2019).…”
Section: Introductionmentioning
confidence: 99%